2007
DOI: 10.2478/s11535-007-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of pinacidil against adrenaline-induced myocardium injury in guinea pig liver mitochondria

Abstract: Abstract:We investigated the role of the ATP-sensitive potassium channel opener pinacidil and blocker glibenclamide on guinea pig liver mitochondrial function, and a possible significance of pinacidil in the pharmacological treatment during myocardium dystrophy. First, a series of experiments was performed to determine the effect of pinacidil and glibenclamide on mitochondrial oxygen consumption. We found that pinacidil increased the rate of mitochondrial respiration for FAD-generated substrate (succinate oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…It has been speculated that the opening of these channels during ischaemia and early reperfusion would produce ADP shortening, reducing Ca 2+ influx and consequently preventing Ca 2+ overload. Our previous studies have shown that protection induced by KATP channel openers was mediated by α-ketoglutarate oxidation and inhibition of lipid peroxidation during stress conditions (27). Our results showed that pharmacological treatment with KATP channel openers induced protective effect during stress conditions and dystrophy in the liver and myocardium of rats and guinea pigs (28).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…It has been speculated that the opening of these channels during ischaemia and early reperfusion would produce ADP shortening, reducing Ca 2+ influx and consequently preventing Ca 2+ overload. Our previous studies have shown that protection induced by KATP channel openers was mediated by α-ketoglutarate oxidation and inhibition of lipid peroxidation during stress conditions (27). Our results showed that pharmacological treatment with KATP channel openers induced protective effect during stress conditions and dystrophy in the liver and myocardium of rats and guinea pigs (28).…”
Section: Introductionsupporting
confidence: 56%
“…We demonstrated a statistically significant decrease in SOD and CAT activity only in the heart of LR animals after administration of Co. These two types of animals: HR and LR were previously shown to exhibit two different functional and metabolic patterns (2,27,28). They are associated with typical differences in the activity of the central nervous system and neuro-humoral regulation, stress-activating and stress-limiting systems, oxygentransporting function of the blood and the state of membranes or receptors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation